2013
DOI: 10.1007/s11307-013-0655-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Arginine Deiminase Treatment in Melanoma Xenografts Using 18F-FLT PET

Abstract: Purpose This study aims to develop a molecular imaging strategy for response assessment of arginine deiminase (ADI) treatment in melanoma xenografts using 3′-[18F]fluoro-3′-deoxythymidine ([18F]-FLT) positron emission tomography (PET). Procedures F-FLT response to ADI therapy was studied in preclinical models of melanoma in vitro and in vivo. The molecular mechanism of response to ADI therapy was investigated, with a particular emphasis on biological pathways known to regulate 18F-FLT metabolism. Results P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
(39 reference statements)
0
10
1
Order By: Relevance
“…This is in contrast to recent work with ADI-PEG20 in ASS1-negative melanoma xenografts in which there was no effect on TK1 expression and FLT-PET metabolic responses were not detected (41). These and previous results using 2 [ 18 F]fluoro-2-deoxy-D-glucose tracers may be explained in part by the differential regulation of ASS1 promoter with HIF-1a-mediated repression in melanoma compared with epigenetic silencing identified in several other arginine auxotrophic cancers (9,16,42).…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to recent work with ADI-PEG20 in ASS1-negative melanoma xenografts in which there was no effect on TK1 expression and FLT-PET metabolic responses were not detected (41). These and previous results using 2 [ 18 F]fluoro-2-deoxy-D-glucose tracers may be explained in part by the differential regulation of ASS1 promoter with HIF-1a-mediated repression in melanoma compared with epigenetic silencing identified in several other arginine auxotrophic cancers (9,16,42).…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, we and others have explored FLT as an alternative imaging PET tracer and although this does not appear predictive in ASS1-negative melanoma, our studies confirmed robust suppression of FLT uptake following ADI-PEG20 treatment of ASS1-methylated tumors [20,106]. Moreover, the uptake of FLT correlated directly with thymidine-kinase 1 (TK1) protein levels consistent with the mode of action of ADI-PEG20 in modulating protein turnover.…”
Section: Imaging Arginine Depletion In Human Cancermentioning
confidence: 54%
“…One of the drawbacks in imaging some arginine auxotrophs such as melanoma, is the apparent increase in glucose uptake following ADI-PEG20 therapy secondary to PTEN loss and PI3K-induced glucose transporter type 1 (GLUT-1) expression [ 47 ]. Thus, we and others have explored FLT as an alternative imaging PET tracer and although this does not appear predictive in ASS1-negative melanoma, our studies confirmed robust suppression of FLT uptake following ADI-PEG20 treatment of ASS1-methylated tumors [ 20 , 106 ]. Moreover, the uptake of FLT correlated directly with thymidine-kinase 1 (TK1) protein levels consistent with the mode of action of ADI-PEG20 in modulating protein turnover.…”
Section: Imaging Arginine Depletion In Human Cancermentioning
confidence: 58%
“…34 Importantly, the effects of combination chemotherapy are likely to be tumor cell type specific, as evidenced by the differential modulation of enzymes involved in nucleotide synthesis after treatment with ADI-PEG20 in mesothelioma compared with melanoma. 11 , 35 In the case of platinum agents, resistance has been observed in ovarian cancer and NSCLC cell lines displaying loss of ASS1, whereas ADI-PEG 20 has been shown to induce cisplatin sensitivity in the latter. 9 , 36 Further work will be needed to optimize antimetabolite combinations on the basis of careful biomarker analyses to identify the role of arginine deprivation in the clinic.…”
Section: Discussionmentioning
confidence: 99%